Species Diversity of Mosquitoes and Environmental Factors as Potential Risks for Dengue Hemorrhagic Fever (DHF): A Literature Review - Pradnyandari, Ida Ayu Tika; Nurjazuli, Nurjazuli; Martini, Martini (Griya Eka Sejahtera, 2025)
Background: Dengue Hemorrhagic Fever (DHF) remains a significant public health problem in Indonesia, with epidemiological patterns that continue to change. This research aimed to examine the diversity of dengue vector mosquito species as well as environmental factors that contribute to the increase in dengue cases.Methods: Literature review by analyzing 11 articles that met the inclusion criteria, obtained from Google Scholar and ScienceDirect (2017-2024).Results: Aedes aegypti and Aedes albopictus are the main species in the spread of dengue fever, with distribution influenced by environmental factors such as temperature, humidity and vegetation cover. In addition, climate change plays a role in increasing the risk of the spread of dengue fever.Conclusion: A deeper understanding of mosquito diversity and their habitats can support more effective vector control efforts